Implementation of feed intervention strategies for improved livestock nutrition and productivity in Mai Son district, Son La province, Vietnam - Atieno, Mary Otieno; Bùi Văn Tùng; Phan Huy Chương; Trần Thị Bích Ngọc; Mai Thanh Tú; Duncan, Alan J.; Douxchamps, Sabine; Peters, Michael (Bioversity International and the International Center for Tropical Agriculture, 2021)
Livestock production in Vietnam is critical in reducing poverty and increasing income particularly for ethnic minorities in the Northwest Highlands. Improved livestock management and productivity can be achieved through better feed management and increased cultivation of improved forages, to meet animal nutrition demand. This study aimed at assessing feed intervention strategies to address context-specific feed-related challenges, mainly winter-feed shortage, for improved animal nutrition and livestock productivity in Mai Son district, Son La province, Vietnam. These interventions included promoting the uptake of improved forage varieties (grasses and legumes) and capacity building on animal nutrition techniques including feed processing and preservation, feed mix and feeding regimes for cattle and pigs. Willing farmers selected various forage varieties, were provided with seeds and planting materials to grow on their farms and guided on forage planting, management, and utilization. Local partners and stakeholders supported various activities and ensured successful implementation amidst the restrictions arising from the Covid 19 pandemic. Farmers reported increased awareness on feed technologies, increased yield, and availability of high-quality feed for their livestock, as well as challenges encountered in applying different feed-related techniques. Initial results from this study show the potential of feed and forage technologies in improving livestock productivity and lays a foundation for scaling these interventions to other regions of Vietnam.